Wake Instabilities of Tip-Loaded Propellers: Comparison between CLT and “New Generation” CLT Configurations - Stefano Gaggero; Marco Ferrando (Journal of Marine Science and Engineering, 2023)
Tip loading is a common strategy to increase the propulsive efficiency of propellers. Solutions such as contracted and tip-loaded (CLT) and “New generation” CLT propellers exploit the presence of an endplate (“true” or as the result of a dedicated modification of the rake distribution) to sustain the increased load at the tip of the blade, at the cost of more complex vortical structures. Their evolution, and the mutual interaction of secondary vortices originated by the endplate itself, however, has not been completely and deeply investigated. The current paper addresses this topic by improved delayed detached eddy simulations (IDDES) of the flow field around two propellers of this type at different loading conditions. The presence of secondary vortices from the endplate root (or from the bended blade at tip), partially observed in recent experiments, is evidenced by high-fidelity CFD calculations. The interaction mechanism with the primary vortices (those from the endplate tip), and the resulting strengthening of the vortical structures, also through the interaction with the blade trailing vortical wake that promote the leapfrogging phenomenon, is discussed as well, comparing the phenomena in the case of two optimally designed geometries (a CLT and a New Generation CLT propeller) exploiting the same pressure side tip-loading concept in a slightly different way. Results show a rather different instability mechanism depending on the endplate configuration and open the discussion on the effectiveness of splitting a single tip vortex into pairs of vortical structures that may induce similar (or even worse) side effects in terms of pressure minima in the wake and earlier wake destabilization.